The effectiveness of absorption heat pumps application for the increase of economic efficiency of CHP operation; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Luzhkovoy D. S. Dmitriy; Romashova O. Yu. Olga Yurievna; Tubolev A. A. Aleksandr Anatolievich; Kobenko Yu. V. Yury Viktorovich; Riabova E. S. Elena (2017, 2017)
Title screen